The Effectiveness of Predict-Observe-Explain (POE) Based E-Modules to Improve Critical Thinking Skills on Chemical Equilibrium - Ramadani, Yasinta Salsabilah; Nasrudin, Harun (International Journal of Educational Research, 2025)
This study aims to analyze the effectiveness of e-modules based on Predict-Observe-Explain (POE) to improve students' critical thinking skills on chemical equilibrium material. The subjects in this study were students of Senior High School 4 Surabaya. This type of research is pre-experimental with a one-group pretest-posttest design. The research data were obtained from the pretest and posttest results of critical thinking skills. Data analysis technique using the Paired Sample t-Test. The study’s results based on the Paired Sample t-Test showed a P-Value of 0.000 (<0.05). Thus, it can be concluded that e-modules based on POE are effectively used to improve students' critical thinking skills on chemical equilibrium material.